'We're in Asia': Worlding LGBTQI+ activism otherwise in Sydney. (May 2021) - Ruez, Derek
Building on recent work in postcolonial urban studies that has developed more genuinely plural approaches to urban theorising, this article poses the problem of 'worlding' in relation to urban LGBTQI+ activism in Sydney, Australia. Specifically, the article examines how Sydney is variously worlded as or against 'Asia' in public debate around LGBTQI+ politics and in the imaginaries of activists living in Sydney. These worldings are shown to be an important aspect of queer activisms and urbanisms in Sydney, and I argue that attention to this worlding can productively complement a renewed focus on place and specificity in queer urban literatures. While imagining Sydney or Australia as part of Asia is itself no guarantee of productive politics or of decentring epistemologies, the article argues that some of these worldings do provide an occasion and a provocation to think elsewhere and otherwise in ways that are responsive to the specific character of White Australia's colonial pasts and presents, while also generatively (dis)locating Sydney beyond the 'West'.